A SYSTEMATIC REVIEW ON MOBILE ASSISSTED LANGUAGE LEARNING IN ENGLISH LANGUAGE TEACHING - Iin Inawati; Cindi Martina Marbun; Bambang Widi Pratolo (ELTIN Journal, 2023)
This study seeks to analyze and synthesize empirical studies on the use of mobile technology in English language teaching. The following criteria were used to select the research articles for this study: (1) peer-reviewed studies, (2) the field of the study must be the implication of MALL, (3) published within the last five years, and (4) studies must be in Asian context. A total of twenty-five published research articles were reviewed in terms of research design, learning context, participant, and settings. The electronic searches for these studies were conducted using search engine databases (e.g., ERIC and Google Scholars) as well as some reputable journal websites (e.g. link.springer.com). The results showed that most of the studies reviewed are mixed-methods and were mainly conducted in Indonesia. The finding also revealed four common topics including the use of MALL was motivating, increasing students’ performances, supporting language learning, and the challenges students face due to Mobile Assisted Language Learning. Overall, the findings indicated that Mobile Assisted Language Learning had a positive impact on the educational context, particularly in English language teaching. Keywords: English Language Teaching, Mobile assisted language learning, English language teaching, Mobile Technology